spatial deixis in kurdish: a cognitive-pragmatic approach - Mohammad Azizi; Rahman Veisi Hasar (پژوهشنامه ادبیات کردی, 2019)
In this article after introducing different deixis, we analyze Kurdish deixis through cognitive semantics. the main focus of the paper is on demonstrative and spatial adverbs among various elements which function as deixis. through this paper we show that the in third person singular pronouns in Kurdish the concept of distance is encoded. far distance encoding is done via the demonstrative /ʔɐw/ if only it is in contrast to the demonstrative /ʔɐm/ in such away that these two are in contrast to each other in an utterance or to be in a question and its answer by the speaker and audience. the only exception is where the speaker is in the figure insead of the ground. distance encoding in four main deixis /ɐmɐ/، /ʔɐwɐ/،/ʔɐmɑnɐ/،/ʔɐwɑnɐ/ are influenced by their derivation of third person singular pronoun and their encoding is the same as the third person singular pronoun. the meaning and range, refered by spatial deixis /ʔɐenɐ/ and /ʔɐeɾɐ/ is not recognized exactly and results in ambiguity which causes a relativity in the boundary. so the boundary intended by the speaker is not exactly what the audience understand and is conveyed via the situation context. furthermore, the speaker's figure when using spatial deixis and the relationship between spatial deixis and motion verbs are probed.